Assessment Of The Level Of Fiscal Sustainability Of Selected European Union Member States In 2014, 2017, 2020 And 2023 - Konopka, Paweł; Łapińska, Patrycja (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Fiscal sustainability constitutes a fundamental prerequisite for the long-term stability of public finances and the resilience of economies to external disturbances. Successive global and regional crises, including the global financial crisis, the sovereign debt crisis, the COVID-19 pandemic, as well as the energy and security shocks related to geopolitical developments, have exposed the vulnerability of fiscal systems within the European Union (EU). States characterized by a higher degree of fiscal sustainability were able to mitigate the adverse macroeconomic and social effects of such crises more effectively, whereas fiscally weaker economies experienced prolonged instability and higher adjustment costs. Consequently, the assessment of fiscal sustainability acquires not only theoretical but also practical significance for shaping fiscal governance. While the subject has been widely discussed in the literature, existing studies frequently focus on single indicators or limited periods, which underscores the need for multidimensional and comparative analyses conducted within a longer time horizon. Aim: The principal objective of this article is to identify the key determinants of fiscal sustainability and to evaluate its level across EU Member States in 2014, 2017, 2020, and 2023. By applying an integrated, synthetic measure, the study addresses the identified research gap, offering a comprehensive and temporally consistent framework for the comparative assessment of fiscal sustainability among EU economies. Results: The Synthetic Measure of Fiscal Sustainability (SMFS) was constructed by employing the modified Hellwig method with Mahalanobis distance. The analysis incorporated five diagnostic variables: the public debt-to-GDP ratio, the budget balance-to-GDP ratio, the GDP growth rate, the current account balance, and EMU bond yields. Empirical data were derived from Eurostat. Hierarchical cluster analysis was subsequently applied to classify Member States into homogeneous groups according to their fiscal sustainability levels. The results indicate that Germany maintained the highest level of fiscal sustainability throughout the examined period, followed by the Netherlands and Malta. In contrast, Greece recorded the lowest SMFS values in 2014 and 2017, France in 2020, and Ireland in 2023. Overall, five distinct clusters of countries were identified, ranging from low to high sustainability. The findings demonstrate significant heterogeneity within the EU and underscore the necessity of designing fiscal frameworks that are both country-specific and consistent with the requirements of supranational fiscal governance.